Development of Community Well-being Action Mechanisms: Lessons from the Provincial Management Unit Development Project in Sisaket Province: Development of Community Well-being Action Mechanisms: Lessons from the Provincial Management Unit Development Project in Sisaket Province - Grittiyachote, Chayanin; Meesin, Kusuma; Thasanapong, Supaporn; Kaewchandee, Chutamat; Suwanphan, Anuphan (RATANABUTH JOURNAL, 2025)
Community health management is an integrated health care approach addressing physical, spiritual, political, economic, and social dimensions. It involves multiple sectors and requires systematic management. This lesson learned synthesis aimed to: 1) extract key knowledge and lessons from the implementation of Si Sa Ket Province Management Mechanism Development Project in terms of road safety management and reduction of alcohol consumption; 2) analyze success factors and limitations of using management mechanisms in driving community well-being work; and 3) develop effective policy recommendations and models for driving community well-being work. The study employed a mixed-methods approach, using document review, in-depth interviews, focus group discussions, participant observations, and analysis of quantitative data from provincial health databases. The research framework applied the Social Ecological Model and Network Governance concepts to analyze driving mechanisms. The results showed that: 1) Key knowledge and lessons learned revealed that effective community health management requires mechanisms that integrate cooperation between various sectors through the use of evidence-based data, team capacity development, and community participation building; 2) Success factors included team capacity, comprehensive community participation, integration of working mechanisms appropriate to local contexts, and support from external agencies, while limitations included mechanism sustainability, inter-agency coordination, and deep-rooted attitudes in local culture; 3) Effective policy recommendations and models for driving community well-being work included the road safety management model using the Road Safety Directing Center mechanism and the alcohol consumption reduction model using the District Health Assembly mechanism, which can be applied in similar contexts.